Pengembangan E-LKPD Berbasis Discovery Learning untuk Meningkatkan Kemampuan Analisis Siswa pada Materi Hormon dalam Reproduksi Manusia - Putri Agustina Anggreni Arwira; Efrida Pima Sari Tambunan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a Discovery Learning-based electronic student worksheet (e-LKPD) that is valid, practical, and effective in improving students' analytical skills on the topic of hormones in the human reproductive system. The method used in this study is research and development (R&D) by adapting the 4D model: define, design, develop, and disseminate. Research instruments included needs analysis, expert validation sheets, and teacher and student response questionnaires. The results show that the developed Discovery Learning-based e-LKPD meets the criteria of validity, practicality, and effectiveness. In conclusion, the e-LKPD is suitable to be used as a learning tool that facilitates the development of students' analytical skills. Keywords: Discovery Learning, E-LKPD, Analytical Skills